2016
DOI: 10.5858/arpa.2016-0009-oa
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the New American Society of Clinical Oncology/College of American Pathologists Guidelines for HER2 Testing by Fluorescence In Situ Hybridization: Experience of an Academic Consultation Practice

Abstract: Context .- Evaluation of HER2 gene amplification by fluorescence in situ hybridization (FISH) was changed by recent American Society of Clinical Oncology/College of American Pathologists (ASCO-CAP) guidelines. Objective . -To determine frequencies and assess patterns of HER2 protein expression for each ASCO-CAP guideline FISH category among 7526 breast cancers accrued to our consultation practice. Design .- We retrospectively reevaluated the HER2 FISH status of breast cancers in our consultation practice accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 25 publications
4
46
1
Order By: Relevance
“…In our study, equivocal HER2 results approached 4% of the total cases with HER2/CEP17 ratios < 2. This rate is similar to those reported by others . In comparison with HER2‐negative cases, we have demonstrated that HER2‐equivocal results (ie, HER2 copy number, 4 to < 6) in the absence of trastuzumab‐based therapy have no deleterious effects on patient outcomes.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, equivocal HER2 results approached 4% of the total cases with HER2/CEP17 ratios < 2. This rate is similar to those reported by others . In comparison with HER2‐negative cases, we have demonstrated that HER2‐equivocal results (ie, HER2 copy number, 4 to < 6) in the absence of trastuzumab‐based therapy have no deleterious effects on patient outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…This rate is similar to those reported by others. 12,14 In comparison with HER2-negative cases, we have demonstrated that HER2-equivocal results (ie, HER2 copy number, 4 to < 6) in the absence of trastuzumab-based therapy have no deleterious effects on patient outcomes. In addition, we have demonstrated that the revised HER2 status due to the use of alternative Ch17 probes is not reflective of patient outcomes.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In detail, many different methods use a single HER2 probe to establish the number of HER2 gene copies, but the most powerful recommendation is to use a dual-probe technique, which allows the determination of the HER2 signals ratio to copies of chromosome 17 and HER2 gene copy number [29]. According to the American Society of Clinical Oncology/College of American Pathologists (ASCO/CAP) 2013 guidelines, evaluation of HER2 gene amplification by FISH in GEA is comparable to that applied in breast cancer, in which HER2 amplification has been identified as HER2:CEP17 ratio of ≥2 [30]. Studies about concordance between FISH, CISH and SISH have shown excellent rates of 91%-100%, demonstrating all ISH methodologies as suitable for HER2 amplification testing [30].…”
Section: Methodological Procedures To Identify Human Epidermal Growthmentioning
confidence: 99%
“…According to the American Society of Clinical Oncology/College of American Pathologists (ASCO/CAP) 2013 guidelines, evaluation of HER2 gene amplification by FISH in GEA is comparable to that applied in breast cancer, in which HER2 amplification has been identified as HER2:CEP17 ratio of ≥2 [30]. Studies about concordance between FISH, CISH and SISH have shown excellent rates of 91%-100%, demonstrating all ISH methodologies as suitable for HER2 amplification testing [30]. More recently, bright field ISH techniques (CISH and SISH) have emerged as preferred assays, since they allow the histopathological assessment (i.e., selecting areas with an intestinal component in GEA), also in archived and indefinitely retrieved specimens, similarly to DISH [30].…”
Section: Methodological Procedures To Identify Human Epidermal Growthmentioning
confidence: 99%